Role of endothelium dysfunction in starting immunopathologic response in chronic brain ischemia - G. I. Shumakher; Ye. N. Vorobiyova; Ye. V. Nechounayeva; M. A. Khoreva; R. I. Vorobiyov; O. G. Simonova; I. A. Batanina (Бюллетень сибирской медицины, 2008)
The paper presents results of clinical and laboratory investigation of 106 patients with chronic brain ischemia (CBI) I-II stages (44 males and 62 females). The age of examined patients varied from 38 to 67 years (mean age was 55,6 ± 2,2). The diagnosis of CBI was estimated according to the generally accepted criteria. Results of laboratory investigation of 22 practically healthy people (10 males and 12 females) served as control. The age of control group varied from 35 to 64 years (mean age was 53,2 ± 2,1). Laboratory diagnostics included detection levels of circulating endothelial cells, autoantibodies to encephalitogenic protein, neuron-specific enolase and protein S-100. Reliable changes of immune status as well as signs of endothelium dysfunction was revealed. These indices are expressed in patients with CBI II stage. Direct correlation between intensity of endothelium dysfunction and activity of autoimmune aggression in brain was revealed.